2011
DOI: 10.1063/1.3650788
|View full text |Cite
|
Sign up to set email alerts
|

Different magnetic properties of rhombohedral and cubic Ni2+ doped indium oxide nanomaterials

Abstract: Transition metal ions doped indium oxide nanomaterials were potentially used as a kind of diluted magnetic semiconductors in transparent spintronic devices. In this paper, the influences of Ni2+ doped contents and rhombohedral or cubic crystalline structures of indium oxide on magnetic properties were investigated. We found that the magnetic properties of Ni2+ doped indium oxide could be transferred from room temperature ferromagnetisms to paramagnetic properties with increments of doped contents. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…44 For 10 mol% Eu-doped rh-In 2 O 3 , lattice spacings of 0.276 and 0.159 nm were observed, corresponding to the (110) and (300) planes of rh-In 2 O 3 , respectively, which is consistent with the literature. 64 Fig. 4 shows the diffuse reflectance UV-visible absorption spectra and plots of [αhν] 2 versus hν for the as-prepared, 400 and 700 °C-annealed undoped, 1 mol% and 10 mol% Eu-doped powder samples.…”
Section: Resultsmentioning
confidence: 99%
“…44 For 10 mol% Eu-doped rh-In 2 O 3 , lattice spacings of 0.276 and 0.159 nm were observed, corresponding to the (110) and (300) planes of rh-In 2 O 3 , respectively, which is consistent with the literature. 64 Fig. 4 shows the diffuse reflectance UV-visible absorption spectra and plots of [αhν] 2 versus hν for the as-prepared, 400 and 700 °C-annealed undoped, 1 mol% and 10 mol% Eu-doped powder samples.…”
Section: Resultsmentioning
confidence: 99%
“…It is noticed that the unit cell of Mn 1Àx Ni x WO 4 (x ¼ 0, 0.02, 0.04, 0.06) extends monotonously with the doping content increasing, owing to the ionic radius of Ni 2+ (0.069 nm) slightly larger than that of Mn 2+ (0.067 nm). 31,32 3.2. Magnetic behaviors Fig.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Results showed that these films had negative magneto-resistance and exchange bias coupling, therefore can be used in transparent spintronic applications. Sun et al [213] had studied the influence of Ni 2+ doped cubic or rhombohedral indium oxide (In 2 O 3 ) nanomaterial on magnetic properties. They observed that magnetic properties of transition metal doped indium oxide could be transferred from room temperature ferromagnetisms to paramagnetic properties with increments of doped contents.…”
Section: Spintronic Devicesmentioning
confidence: 99%